Óleos vegetais e óleo mineral na mortalidade da Bemisia tabaci biótipo B e na transmissão do vírus do mosaico dourado no feijoeiro - Marques, Míriam de Almeida (2011)
As an alternative to synthetic insecticides, mineral oils and vegetable oils have been shown to be promising in controlling Bemisia tabaci biotype B. This study aimed to evaluate the effect of mineral and vegetable oils on eggs, nymphs and adults of B. tabaci biotype B, in the transmission of the bean golden mosaic virus and on dry production. The experiments were conducted at screenhouse at Embrapa Rice and Beans, Santo Antônio de Goiás, Goiás. The following oils in the concentration of 1% were used: Assist® mineral oil, Neem Max® neem oil, Veget'oil® vegetable oil, Citrole® orange oil, Castor Oil®, Sesame Oil®. The two last oils were emulsified with detergent Zupp® at 2%. Thiamethoxam at 200 g pc/ha (GD - dispersible granule) was used as a standard for comparison of chemical insecticide and distilled water as control. In all experiments, the experimental unit consisted of a polyethylene pot (34 cm diameter x 12 cm) containing two seedlings of common bean cv. Pearl. The experimental design was completely randomized with four replications / treatment. In the first experiment was evaluated the effect of oils on the mortality of eggs of B. tabaci. The second experiment was conducted to verify that the treatment of eggs with the oils would affect first instar nymphs. In the third experiment was evaluated the mortality of nymphs of the second to fourth instar after spraying of oil on the second instar nymphs. In these experiments, seedlings of bean cv. Pearl infested with eggs or nymphs of the whitefly were sprayed with 250 μL of each treatment on the abaxial surface of leaves. In the fourth experiment, four seedlings infested with adults and distributed in one m2 were sprayed with 30 ml of treatment. In the fifth experiment the effect of oils on adult mortality, the incidence of bean golden mosaic virus and crop production were evaluated by spraying only vegetable oils before the infestation of the seedlings with adults. All treatments caused mortality of eggs lesser or equal to 9.5%. Vegetable oils, when applied to eggs, caused mortality of newly-hatched nymphs lesser or equal to 22.3%. All treatments caused significant mortality of second instar nymphs, ranging from 46.5% for thiamethoxan to 81.6% for to castor oil. The treatments also affected the development of the nymphs until the fourth instar. Mortalities of nymphs greater than 80% were observed with castor, neem, sesame and orange oils. Only castor, sesame and mineral oils caused significant adult mortalities of 41.2%, 25.7% and 38.0%, respectively, one day after spraying. The orange, castor, neem and sesame oils, when sprayed prior to insect infestation of beans seedlings, caused mortality of whitefly adults ranging from 32.1% to 53.6%, one day after application. The castor and orange oils reduced the incidence of golden mosaic virus in bean. Castor oil favored greater pod yield, while the lowest pod yield was observed on sesame oil. The total number of seeds, mean number of seeds per pod and seed weight was not increased with the use of vegetable oils. The use vegetable and mineral oils have the potential to control B. tabaci biotype B.